problems of the Weak Role of the Libyan Audit Bureau in Combating Financial Corruption in Government Units "Survey of Auditors’ Opinions in the Libyan Audit Bureau" (Comprehensive Journal of Science, 2026)
This study investigates the underlying problems behind the weak role of the Libyan Audit Bureau in curbing financial corruption within government units, despite its long institutional history and legal mandate. The research adopts a descriptive analytical methodology, combining documentary analysis of laws, regulations, and annual reports with a field survey conducted through a structured questionnaire distributed to a random sample of Audit Bureau auditor in Tripoli. Out of 120 questionnaires, 97 were valid for analysis, yielding a response rate of 83.62%. Reliability was tested using Cronbach’s Alpha, which ranged between 0.645 and 0.808 across different dimensions, indicating acceptable internal consistency.The findings reveal significant legislative and organizational deficiencies in the regulatory framework governing the Bureau’s operations, as well as the negative impact of its subordination to the legislative authority and prevailing political and security conditions. Moreover, the Bureau’s focus on ex‑post auditing rather than preventive controls, coupled with its limited role in promoting governance practices and encouraging internal audit units, has weakened its effectiveness in combating financial corruption.The study concludes that strengthening the Bureau’s role requires comprehensive institutional and legislative reforms, including the enactment of specific anti‑corruption laws, enhancing the Bureau’s independence, integrating governance principles, and developing auditors’ competencies through continuous training. Aligning Libyan legislation with the United Nations Convention against Corruption and adopting a national preventive strategy are essential to ensure transparency, accountability, and effective protection of public funds.
Keywords: Libyan Audit Bureau, Financial corruption, financial auditing, Governance, Legislative and regulatory framework, Institutional independence, Ex post and ex ante auditing, Internal audit units, Transparency and accountability, Institutional reform